Effect of antitubercular treatment on ovarian function in female genital tuberculosis with infertility - Jai Bhagwan Sharma; J Sneha; U B Singh; Sunesh Kumar; K K Roy; Neeta Singh; Sona Dharmendra (Wolters Kluwer Medknow Publications, 2016)
AIM: To evaluate the effect of antitubercular therapy (ATT) on an ovarian function such as ovarian reserve, ovarian dimensions, and ovarian stromal blood flow. SETTINGS AND DESIGN: Prospective study design. MATERIALS AND METHODS: Fifty infertile women with female genital tuberculosis (FGTB) without tubo-ovarian masses diagnosed by positive acid-fast bacilli culture or epithelioid granuloma on endometrial aspirate or positive polymerase chain reaction with positive findings on laparoscopy or hysteroscopy were recruited. The ovarian function tests were performed on day 2/3 as follicle-stimulating hormone (FSH) levels and anti-Mullerian hormone (AMH) levels. Ovarian dimensions (length, width, and depth) were measured using a transvaginal ultrasound. Mean antral follicle count (AFC) and ovarian stromal blood flow (peak systolic velocity [PSV], pulsatility index (PI), and resistive index [RI]) were measured using a transvaginal ultrasound. All women were started on ATT for 6 months by directly observed treatment strategy. After completion of ATT, all the parameters were repeated. RESULTS: There was a significant increase in AMH (2.68 ± 0.97 ng/ml to 2.8 ± 1.03 ng/ml) pre- to post-ATT, nonsignificant increase in FSH (7.16 ± 2.34 mIU/ml to 7.26 ± 2.33 mIU/ml) post-ATT, significant increase in mean AFC (7.40 ± 2.12-8.14 ± 2.17), PSV in the right ovary (6.015-6.11 cm/s) and left ovary (6.05-6.08 cm/s), PI in the right ovary (0.935-0.951 cm/s) and left ovary (0.936-0.957 cm/s), and RI in the right ovary (0.62 ± 0.01-0.79 ± 0.02) and left ovary (0.65 ± 0.02-0.84 ± 0.01) with ATT. There was no significant change in mean ovarian dimensions (ovarian length, breadth, and width) and summed ovarian volume with ATT. On laparoscopy, tubercles were seen in 27 (54%) women. Caseous nodules and encysted ascites were seen in 8% cases each. CONCLUSION: ATT improves the ovarian function (AMH and AFC) and ovarian blood flow in women with FGTB.